Hereditary Painful Callosities Treated with L5 and S1 Pulsed Radiofrequency, Case Report - Moustafa Moustafa; Kenneth Kuan Boon Keat; Hari Gopal (International Journal of Pain, 2025)
Hereditary palmoplantar Keratoderma (PPK) varies in presentation, where palm and sole lesions can be diffuse, focal or punctate. There is no specific curative treatment for hereditary PPK, and the resulting pain may significantly strain all aspects of the patient’s life, causing significant distress and functional impairment. Treatment of callosities includes topical and systemic medications. Although PRF at the dorsal root ganglia is more commonly used to treat radicular neuropathic pain, its use for non-neuropathic pain progressively increases with promising results. In the following case report, DRG PRF treatment was successfully used to treat complex pain secondary to hereditary painful callosities. A 48-year-old gentleman presented with bilateral isolated congenital callosities, which were extensive in the right foot, causing severe distressing pain with significant negative reflection on his mood and function levels. He struggled with this pain for over 17 years despite trying multiple medical and surgical treatments. We followed a holistic approach by enrolling him in the pain management program and Left L5 and S1 Pulsed Radiofrequency treatment at left L5 and S1 DRGs. The treatment resulted in sustained pain relief for one year, and the patient happily had four repeated injections on an annual basis. The patient reported significant improvement in pain and quality of his life accordingly. PRF treatment of DRGs effectively managed severe non-neuropathic foot pain resulting from hereditary painful callosities. We recommend doing further well-designed randomised clinical trials to study the efficacy and safety of PRF treatment at the DRG for non-neuropathic pain.